Income equalisation: is all fair in primary production and tax law? - Hodgson, Helen; Castelyn, Donovan; Marriott, Lisa (2019)
This article examines income equalisation deposit schemes (IEDSs) in the Australian and New Zealand primary industry sectors. The purpose of such schemes is to assist eligible taxpayers with managing inconsistent cash flows, effectively facilitating income smoothing. The authors explore the policy rationale for these schemes, contrasting New Zealand and Australia, using pluralism as a theoretical framework. The authors note the diminishing economic contribution of the primary sector and the relatively low levels of tax paid by the sector. The findings challenge some of the arguments typically raised in support of preferential tax treatment for the primary sector. The authors’ analysis shows that the farm management deposits scheme in Australia has nearly 50 times as much in the way of funds invested as the equivalent income equalisation scheme in New Zealand. It is proposed that the relatively low top income tax rate and threshold of 33% and $70,000, respectively, in New Zealand are significant factors in the greater use of income equalisation in Australia. Pluralism, in this context, is effective in highlighting the influence of lobby and pressure groups in policy outcomes that are relevant to the primary sector.